Religion Influences Community Adherence to COVID-19 Guidelines in Uganda - Echoru, Isaac; Kasozi, Keneth Iceland; Usman, Ibe Michael; Ssempijja, Fred; Tiyo Ayikobua, Emmanuel; Mujinya, Regan; Ajambo, Patricia Decanar; Matama, Kevin; Monima Lemuel, Ann; Ayuba Tabakwot, John; Ojodale Aruwa, Joshua; Simidi Kegoye, Eric; et al. (Research Square, 2020)
Success of public health government programs depends on effective partnerships between religious institutions, policy makers and medical professionals. Directives from the World Health Organization (WHO) against social gatherings to control COVID-19 transmission have negatively impacted religiouspolitical partnerships. Compliance of rural communities to national lockdowns requires support from community faith leaders. Across the African sub-continent faith plays an important role within communities that display diverse religious practice. Specific guidelines to prevent community transmission and spread of novel coronavirus 2019 (COVID-19) are however, scarce, complicating adherence to best practice as defined by the World Health Organization (WHO). During the Ebola epidemic in Africa, faith groups played a crucial role in spreading information from the WHO to control community disease transmissions. Methods Here we examined knowledge, attitudes and practices for COVID-19 among market vendors, of faith, in South-Western Uganda. A cross sectional study was undertaken among rural market vendors (n=248) in southwestern Uganda was undertaken using an online questionnaire. Results Most moslems (72%) and protestants (70%) were aware that COVID-19 could present symptomatically and the challenges for control of COVID-19 in Uganda. Definitive knowledge of COVID-19 transmission dynamics was most prevalent among individuals of Protestant faith (70%). Most moslems (66%) interviewed found it difficult to comply with public health measures (lockdowns and self-isolation) while most pentecostals (64%) considered wearing as face mask to be impractical. Such discrepancies within a tight knit community and religious groupings in relation to practice shows a need to strengthen and revise policy for the national implementation of COVID-19 guidelines. Conclusion Engagement from religious leaders to encourage their followers to abide to COVID-19 guidelines would facilitate Africa’s COVID-19 response to become more effective addressing key areas of non-compliance that undermine control e.g. a majority of Pentecostal Christians are hesitant to be associated with alcohol-based hand sanitizers.
Keywords: COVID-19; Control; Faith